Development of single reagent for fluorescence polarization immunoassay of atrazine - Choi, MJ; Lee, JR; Eremin, SA (TAYLOR & FRANCIS LTD, 2002)
Fluorescein-labelled s-triazines (tracers), differing in bridge length and structure, were prepared. The binding of the tracers with specific anti-atrazine antibodies were investigated in order to choose an optimal an antigen-antibody pair. Significant differences were found in titre, sensitivity and assay kinetics. A fluorescence polarization immunoassay (FPIA) for atrazine was developed. FPIA is based on the increase in fluorescence polarization of a small fluorescent-labelled tracer when bound by specific antibody. If the sample contains unlabelled atrazine, it will compete with tracer for binding with antibody and the polarization signal will decrease. No separation of free and bound analyte and no wash steps are required. To simplify the FPIA procedure, a pre-equilibrated "single reagent" immunocomplex of antibody and tracer (SR) was prepared. This SR-FPIA provides an exceptionally simple, one-step immunoassay method. Sample is added to the single reagent and displacement of tracer from the immunocomplex is measured after brief (5-10 min) incubation. The detection limit is approximately 3 ng ml(-1) of atrazine in 0.1 ml sample with good precision (CV<3%). The cross reactivities with simazine and cyanazine are 30% and 1%, respectively, and lower than 0.1% for other herbicides tested. The single reagent immunocomplex has proven to be stable as compared with individual solutions of antibody and tracer.
Keywords: S-TRIAZINE HERBICIDES; MOLECULARLY IMPRINTED POLYMERS; LINKED-IMMUNOSORBENT-ASSAY; CHROMATOGRAPHY MASS-SPECTROMETRY; DIODE-ARRAY DETECTION; MONOCLONAL-ANTIBODIES; WATER SAMPLES; SOLID-PHASE; LIQUID-CHROMATOGRAPHY; ENZYME-IMMUNOASSAY